(untitled) (Research, Society and Development, 2021)
Introduction: The central giant cell lesion, also known as central giant cell granuloma, is considered to be a non-neoplastic lesion, which consists of fibrous tissue with multiple foci of hemorrhage, aggregation of multinucleated giant cells and, in some cases, trabeculae of bone tissue, it frequently affects the central region of the mandible, crossing the midline, and corresponds to 7% of all benign lesions of the jaws. Although it can affect a wide age group, it is more common to be seen in patients between 2 and 30 years of age. It has a slight preference for the female sex, with an incidence peak in the age group between 10 and 25 years. Objective: To report the clinical case, as well as discuss the therapeutic approach used, of a central giant cell lesion in the mandible, which worsened after the proposed conservative treatment. Discussion: The treatment of LCCG is traditionally by surgical removal followed or not by curettage. There are also supplementary measures such as cryosurgery or peripheral osteotomy. In cases where major mutilations are predictable, alternative treatments can be used, such as intralesional injections of corticosteroids, calcitonin, subcutaneous or nasal, subcutaneous alpha-2a interferon, imatinib and bisphosphonates. Final considerations: Surgical treatment with partial resection associated with bone reconstruction with autogenous iliac crest bone proved to be efficient in cases of failure of conservative therapy.